Identification and analysis spatial areas of urban poverty in Shahrekord neighborhoods, Iran - Saeed Yousefi Babadi; Hooman Goodarzi (Sustainable Earth Trends)
One of the most important topics in development economics texts is the issue of poverty, measuring and reducing it and poverty alleviation. The first step in planning to fight poverty and reducing inequality is to have a proper understanding of the poverty situation. According to this issue, the purpose of this study is identifying and analyzing urban poverty as well as its spatial distribution in the neighborhoods of Shahrekord and to formulate and present suggestions and solutions appropriate to the approach of organizing human societies in order to address its unhealthy conditions. The present article has taken a cognitive and exploratory approach in terms of purpose and is considered evaluative-comparative in terms of method that after explaining the concept of urban poverty with the help of quantitative and qualitative data (statistical block 2016, Upstream plans, land use maps, etc.) of 40 indicators in the form of four main economic, social, cultural and physical variables has been classified using TOPSIS and AHP methods and has identified and distributed the spatial distribution of urban poverty in Shahrekord neighborhoods with ARC GIS software. Urban poverty was addressed in Shahrekord neighborhoods and a map of poverty distribution was drawn. The results show that Koreh, Borveh Pahneh, Darb Darreh, Ashtaftak and Mahdieh neighborhoods were identified as poor and targets for planning.